Spacing and geometric layout effects on the productivity of clonal Eucalyptus plantations - Stape, Jose Luiz [UNESP]; Silva, C. R.; Binkley, Dan (Elsevier, 2022)
The choice of initial spacing (stocking or density) for plantations influences the amount of growth resources available for each tree, rates of growth and survival, and the stand-level wood production and profit. A given number of trees per hectare can be arranged in various geometric ways, with designs varying the spacing between planting rows, and the distance between trees within rows. Large distances between rows lower costs of site preparation, but tight packing of trees within rows may limit light interception, leading to rapid forest stratification (into dominant and suppressed classes) and increasing risks of weed competition and wind damage. We evaluated the effects of spacing (m2 tree−1) and geometric layout (distances between rows, and between trees within rows) on the productivity of two Eucalyptus grandis x E. urophylla clones. A complete 2 × 3 × 3 factorial design was applied to two clones, with three spacing levels (6.0, 10.5 and 15.0 m² tree−1) and 3 between-row distances (3, 6, and 9 m). After 6 years, Clone 1 was 11% more productive (MAI 33.8 m³ ha−1 yr−1) than Clone 2 (MAI 30.5 m³ ha−1 yr−1), largely owing to greater wind damage of Clone 2 (especially at wide between-row spacings). The highest growth for both clones occurred at the densest spacing (6.0 m² tree−1), with a yield of 212 m³ ha−1. Greater spacing lowered stand yield by 10% (10.5 m² tree−1) to 18% (15.0 m² tree−1). Increasing distances between rows (coupled with decreasing distances between trees within rows) also decreased yields, dropping by 16% as between-row distance increased from 3 to 9 m. High densities of trees planted in a square design gave the greatest yields.